ORGANIZATIONAL POLITICS AND EMPLOYEE SUPPORT: EVIDENCE FROM ENUGU STATE MINISTRY OF LANDS AND URBAN DEVELOPMENT - Okafor, Lawrence Chima; Okorie, Ebere Florence; Aikhomu, John; Egbo, Vincent Ozoemenam (EBSU Journal of Social Sciences and Humanities, 2023)
This study, organizational politics and employee support in Enugu State Ministry of Lands and Urban Development, Enugu was aimed at ascertaining the relationship between organizational politics and employee support. 123 employees of the ministry participated in the study. 112 responses were used to generate data for the analysis. Pearsons’ product moment correlation with the aid of SPSS version 23.0 was used to ascertain the relationship which was used to test the stated hypotheses. The result indicated a significant negative relationship between Line vs Staff game and employee support. Rival camp game has a significant negative relationship with employee support; Expertise game equally indicated a significant negative relationship with employee support. We therefore concluded that organizational politics has a significant negative relationship with employee support. The implication of these findings is that political behaviourin an organization is inevitable. Moreover, its practice in the context of organization with diverse workforce as it pertains to experts/professionals manifests in various games which could divert employees attention towards self-interest to the detriment of the entire organization. We recommended that proper check should be put in place to ensure that political games do not get too personal within the ministry as it gradually wanes support amongst employees.